BIOLOGICAL SURFACE ACTIVE COMPOUNDS APPLICATION POSSIBILITIES AND SELECTION OF STRAIN WITH EMULSIFYING ACTIVITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The biological oil- polluted soil treatment method is used widely; however it is not effective enough because the microorganism‟s metabolism is affected by seasonal temperature fluctuation. Besides, soil remediation processes are very slow because of low solubility of oil and oil products in water. Biological surface active compounds show promising results in oil-polluted soil bioremediation. Three hydrocarbons degrading microorganisms strains, showing high emulsification activity were selected.